POLITIK PENGAWASAN DPRD DALAM UPAYA PEMAKZULAN KEPALA DAERAH : Studi Kasus Wali kota Surabaya - Amalia, Luky Sandra (Pusat Penelitian Politik, 2011)
Impeachment as apublic officialproceedings conducted byparliament has become a quitepopular discourselately despite the impeachment efforts that occurred over many issues associated with interparty rivalry ratherthan as a process ofparliamentary oversight Impeachment in the context oflndonesian politics under the existingconstitution can only be carried by the House ofRepresentatives against the President Vice President on the basisofcertain reasons such as violation of law national treason corruption and others The impeachment which iscarried by District Legislative Council of Surabaya against the local mayor can be an interesting case becauseof besides there is no legal basis under the constitution the process becomes a new precedent in the political dvnamics of the local parliament This paper attempts to explore the District Legislative Council impeachment casecomprehensively The case is to be analyzedfrom aspect of regulation and process as well as political motivesbehind the impeachment effort This paper will also unravel the dynamics that occur in the impeachment processand its impact on parliamentary politics at the local level